Pro-oxidant antioxidant balance in patients with non-alcoholic fatty liver disease - Nobakht Motlagh Ghoochani, Bibi Fatemeh (Gastroenterol Hepatol Bed Bench, 2019)
AIM: We aimed to determine these parameters in patients with non-alcoholic fatty liver disease using pro-oxidant antioxidant balance assay. BACKGROUND: In human, pro-oxidants and antioxidants are normally produced and there is a balance between production and deletion of them. When the balance between oxidants and antioxidants are disrupted oxidative stress occurs. Oxidative stress is known one of the main mechanisms for the development of nonalcoholic fatty liver disease. Many investigations have evaluated some oxidants and/or antioxidant status in these patients. However, studies explaining the antioxidant status and the oxidant burden in these patients are lacking. METHODS: Sera from 35 healthy subjects and 38 patients with non-alcoholic fatty liver disease were recruited. Then, the pro-oxidant burden and the antioxidants capacity were measured by pro-oxidant antioxidant balance assay. RESULTS: There was no significant difference in the mean pro-oxidant antioxidant balance values between the two study groups. The results demonstrated that serum pro-oxidant antioxidant balance values were positively correlated with BMI and age in the patient group. Furthermore, the pro-oxidant antioxidant balance significantly increased in women when compared with men in all participants. CONCLUSION: It demonstrated that increased antioxidant status could be as a response reflecting of the organism to elevated oxidants in NAFLD patients which may lead to unchanged PAB values.